A Comparative Study on Wealth Effects of Sukuk and Conventional Bonds - Haque, Mohammad Aminul (2013)
The legendary growth of Sukuk for last decade along with the lack of previous in depth studies were the motivating factors for this study on the wealth effect of Sukuk and conventional bond announcement and their determinants during the event window -3 to +3 surrounding the announcement date of the bond issuance. It is revealed that the market reaction is negative for the announcements of Sukuk before, during and after global financial crisis. On the other hand market reaction is positive for announcement of conventional bond only after the global financial crisis period and the market reaction is negative before & during global financial crisis period for the conventional bonds. Study is also conducted considering overall period from 2004 to 2012. For the overall period, market reaction is negative for both Sukuk and Islamic bond. Four independent variables are suggested by previous literature review, namely firm size, free cash flow, leverage and the Shahriah compliant status as the explanatory variables of the wealth effect. For overall period, free cash flow has significant negative impact on wealth effect. For the time period of before global financial crisis, firm size has got significant positive impact on wealth effect. During global financial crisis, no such significant relation found. Finally, after the global financial crisis peiord, free cash flow has got significant negative impact on wealth effect and leverage has got significant negative impact on wealth effect. Expect those variables; others are not significant on wealth effect during the mentioned time periods. Therefore, the independent variables has got different impact on the wealth effect in before, during and after the global financial crisis.